Youth employability and work attitudes - Abd. Rokis, Rohaiza (International Journal of Science Commerce and Humanities, 2014)
Youth employability is often hindered by a lack of good work attitude among young people. This article anticipates that the attitude towards work is indicative of the youths’ future behavior at work. It is derived from a research project that used the stratified sampling technique on 159 respondents and 10 interviewees from Program Latihan Khidmat Negara(PLKN). The analysis strategy of the research depends on the anomalous cases of the youth attitudes towards the 9-work attitude construct. The results found correlations between age and the 9-work attitude construct. They chose work that offers less workload, less competition, and is less stressful, but offers high income. They were also less creative artwork, uncompromising, indeterminate and complacent. In terms of emotional aspect, the respondents revealed that they were easily annoyed and impatient at work, and were unable to work under pressure. The study anticipates their difficult employability situation in the future.